Empowering and Fostering Creative Industries Entrepreneurs Based on Local Wisdom of Malay Deli - Juliana Juliana; Fatimah Fatimah; Apriliyanti Apriliyanti (Karsa: Journal of Social and Islamic Culture, 2018)
This research aimed to provide an empowerment medium to the people of Medan city through fostering graffiti drawing  base on the local wisdom of Malay Deli as a form of creative entrepreneurship. Employing a qualitative method, this research collected the data through observation, interview and documentation. The results showed that graffiti art creativity may be used as a medium to introduce and revitalize Malay Deli local wisdom values through the use of the icon Pak Belalang and Malay Deli Pantun. The icon Pak Belalang in this research served  to be an informative, communicative and motivative icon in introducing and preserving Malay Deli Pantun. Malay Deli Pantun in this research has the local wisdom values of Malay Cultures such as moral values including the values of responsibility, tolerance, hard work, democratic and nationality, ethical values including the values of cleanliness, security,order, beauty and kinship and norms values including the norms of legal, morality, decency, and habit. Therefore, it can be concluded that empowering and fostering Medan people to become independent and creative entrepreneurs can be conducted by optimising the graffiti drawing creatifity in making the souvenirs based on local wisdom of Malay Deli using Pak belalang icon and pantuns of Malay Deli.